"Signal‐on" Electrogenerated Chemiluminescence Biosensing Method for the Determination of Matrix Metalloproteinase 2. Issue 2 (23rd August 2021) - Zhang, Mengyu; Shi, Liang; Liu, Xiaoru; Qian, Manping; Qi, Honglan
Abstract: A simple, selective and sensitive "signal‐on" electrogenerated chemiluminescence (ECL) biosensing method was developed for matrix metalloproteinase 2 (MMP‐2). Ru(bpy)3 2+, gold nanoparticles (AuNPs) and Nafion were modified onto glassy carbon electrode (GCE) to form Ru(bpy)3 2+ /AuNPs/Nafion/GCE as sensitive ECL platform and then ferrocene (Fc) labeled peptide was assembled onto the modified electrode to form ECL biosensing platform. The ECL intensity increased when the ECL biosensing electrode reacted with MMP‐2 because of MMP‐2‐induced cleavage of Fc labeled peptide. The ECL method was applied to determine MMP‐2 with detection limit of 0.3 ng/mL and one‐step recognition, which is promising for point‐of‐care test of protease. Abstract :